Diagnostic overshadowing in learning disability: think beyond the disability. Issue 2 (13th May 2019) - Javaid, Amir; Nakata, Vera; Michael, Dasari
Abstract : Diagnostic overshadowing is increasingly recognised as contributing to health inequalities experienced by the learning disability population. This case is that of a 54‐year‐old male with mild‐to‐moderate learning disability who displayed abnormally aggressive behaviours and self‐neglect. He had multiple transfers between the psychiatric and medical units during an inpatient episode, partly due to his physical health symptoms being misattributed to learning disability and challenging behaviour.